Consumers’ Purchase Intention of Organic Food via Social Media: The Perspectives of Task-Technology Fit and Post-acceptance Model - You, Jun-Jer; Jong, Din; Wiangin, Uraiporn (Frontiers in Psychology, 2020)
In the past, consumers were mainly informed about organic food by newspapers, magazines and television advertisements. However, when consumers buy organic products in the market, they cannot get complete information about the products from the appearance of the various products. In order to overcome this information asymmetry, social media has become an indispensable part of the promotion of organic food by providing a clear distinction between certified organic products and other types of products in the market. The purpose of this study is to demonstrate the antecedents and consequences of the influence of social media on consumers' selection of organic food, based on the post-acceptance model (PAM) and task-technology fit model. The empirical results indicated task characteristics and technology characteristics had the significant effects on confirmation of expectations and perceived usefulness through task-technology fit. Besides, confirmation of expectations and perceived usefulness also influenced significantly satisfaction and continuance intention respectively. Finally, the results presented in this article would contribute to the practical and academic implications and recommendations on the promotion of organic food in social media platform.